CLDN18.2: a potential nanotherapeutic target for cholangiocarcinoma - Huang, Yu; Ye, Yulu; Yi, Tingzhuang; Yuan, Cheng; Li, Daojun (Frontiers in Pharmacology, 2025)
Cholangiocarcinoma (CCA) is an extremely malignant and aggressive primary liver tumor that has become increasingly prevalent in recent years. Unfortunately, the prognosis for patients diagnosed with CCA remains exceptionally poor. Currently, the primary treatment options include surgery and chemotherapy. However, the effectiveness of postoperative chemotherapy is limited, characterized by a brief duration of remission and high rates of recurrence and metastasis, resulting in minimal survival benefits for patients. Therefore, there is an urgent need to develop new therapeutic strategies that are both safer and more effective. In recent years, as oncology research has progressed, Claudin 18.2 (CLDN18.2)-targeted therapy has emerged, showing promise for improving the survival of patients with CLDN18.2-positive cancers. Studies suggest that combining new agents targeting CLDN18.2 with standard cytotoxic therapies offers significant survival benefits in CLDN18.2-positive solid tumors, which is expected to provide a more effective treatment option for patients with advanced cholangiocarcinoma. While existing immune checkpoints or therapeutic targets have limitations, such as low positivity rates and minimal absolute improvement in patient survival time, drugs that target FGFR, IDH, and Her-2, along with antiangiogenic agents, have shown promise for patients with advanced malignancies affecting the bile ducts. Therefore, exploring these novel therapeutic strategies may yield new insights for precision treatment of cholangiocarcinoma in the future. This review aims to focus on the potential application of CLDN18.2 in treating solid tumors, particularly cholangiocarcinoma, to systematically summarize research progress related to this target and thoroughly examine its value in diagnosing, treating, and assessing the prognosis of cholangiocarcinoma.